Virtual Sphere: A Site to Negotiate the Image of Lengger Banyumas - Lynda Susana Widya Ayu Fatmawaty; Condro Nur Alim (Bina Nusantara University, 2020)
The research aimed at investigating how Lengger used the virtual sphere to negotiate their image to society. LenggerBanyumas was always stereotyped with the discourse of Queer, Gay, Bisexual, and Transgender (QGBT). Therefore, it ledto gender discrimination, not only on the stage but also in their daily life. Consequently, in this 4.0 era, Lengger neededto use social media in order to create a different image as an alternative way to negotiate the dancer’s gender identity.The method applied was Hine’s virtual ethnography method by applying Habermas theory. Respondents were interviewed virtually through video conference. Meanwhile, the data were collected through their Instagram. The results show that Lengger constructs their image on social media to produce an image by performing double-identity; they are feminine on the stage and masculine in real life. The first identity is a feminine dancer to reveal the image of a professional drag dancer from Banyumas. However, Lengger elaborates the masculine identity in their dance performance by wearing the attribute of female dancers. Meanwhile, Lengger also reveals masculine identity in their real life. As identity is fluid, it indicates that the image will also never be fixed. Thus, this image is reproduced constantly in the virtual sphere as a negotiation towards society’s stereotyping.